(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The quinazolinone moiety is a significant pharmacophore depicts various types of pharmacological activities as shown in recent exhaustive ligatures serve. Quinazolinone exhibit potent central nervous system (CNS) activities like anti-anxiety, analgesic, anti-inflammatory and anticonvulsant. To develop these views and application profiles, attempt have been made to report a drug/ligand or receptor/protein interactions by identifying the suitable active site against X-ray crystal structure of Human Carbonic Anhydrase II (HCA II) enzyme for anticonvulsant activity using Vlife MDS version 4.6 Software because the protein-ligand interaction plays a significant role in structural based drug designing. The interaction was evaluated based on the score comparison between quinazolinone derivatives with sugar sulfamate. The quinazolinone ring forms hydrophobic and hydrogen bond contacts amino acid residues. The ligands 4t and 4s were shown to possess minimum dock score i.e. minimum binding energy in Kcal/mole i.e. these molecules has more affinity for active site of receptor. Clearly, Molecules having low dock score and binding energy shows more affinity towards the receptor. The data reported in this article may be helpful for the medicinal chemists who are working in this area.